2008
DOI: 10.1111/j.1442-2050.2007.00772.x
|View full text |Cite
|
Sign up to set email alerts
|

Time course of necrosis/apoptosis and neovascularization during experimental gastric conditioning

Abstract: Apoptosis, necrosis and neovascularization are three processes that occur during ischemic preconditioning in a range of organs. In the stomach, the effect of this preconditioning (the delay phenomenon) has helped to improve gastric vascularization prior to esophagogastric anastomosis after esophagectomy. Here we present a sequential study of the histological recovery of the gastric fundus and the phenomena of apoptosis, necrosis and neovascularization in an experimental model of partial gastric ischemia. Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 29 publications
(54 reference statements)
4
36
0
Order By: Relevance
“…After ligation of the left gastric vessels, there seems to be an immediate diversion of blood toward the greater curve of the stomach, which mirrors the observations made by other researchers [22,23,32,34]. Dilatation of the right gastroepiploic arcade has been demonstrated on angiography and histology after ischemic conditioning of the stomach.…”
Section: Conclusion and Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…After ligation of the left gastric vessels, there seems to be an immediate diversion of blood toward the greater curve of the stomach, which mirrors the observations made by other researchers [22,23,32,34]. Dilatation of the right gastroepiploic arcade has been demonstrated on angiography and histology after ischemic conditioning of the stomach.…”
Section: Conclusion and Discussionsupporting
confidence: 73%
“…The upper part of the transposed stomach is particularly at risk from rarefaction of intramural vessels, as demonstrated by anatomical studies [17]. Urschel and others [18][19][20] have explored the role of gastric ischemic conditioning in animals and demonstrated that this may have a potential benefit [21][22][23][24][25][26]. Akiyama in 1992 [27] reported the first human clinical series, and more recent studies have confirmed a beneficial impact of conditioning [28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 89%
“…A 5-day LIC could represent an inadequate time for ischemic conditioning of the gastric fundus (future conduit tip) to take place. This line of thought is backed by the recent work of Lamas et al [21], strongly suggesting the need to delay an esophagectomy until about 2 weeks after ischemic conditioning. Five days may simply be exposing the gastric conduit to ''ischemic stress,'' which becomes more apparent in a proportion of patients (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Numerous animal experiments have pondered the merits of gastric ischemic conditioning [17][18][19][20], most notably the work by Urschel [43], and more recently, the work of Lamas et al [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation